Preparation and Application of Biochar from Areca catechu L. Peel for Malachite Green and Reactive Blue Dyes Removal - Palapa, Neza Rahayu; Putra, M. Bagus Kurnia; Musifa, Eva; Yuliasari, Nova; Adawiyah, Robiatul (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
The utilization of Areca catechu L. fruit peel waste as biochar offers a sustainable solution for waste management while enhancing the material’s value as an efficient adsorbent. Biochar from Areca catechu L. fruit peels was processed through pyrolysis for 2 hours at temperature of 500oC. This study investigates the use of biochar from Areca catechu L. peel as an adsorbent for Malachite Green (MG) and Reactive Blue (RB) dyes in a batch system, with a focus on analysing the kinetic adsorption processes. The biochar was characterized using XRD, FTIR, SEM and BET. BET analysis was conducted, which shows that the surface area of biochar from Areca catheca L. fruit peel after pyrolysis treatment was 29.52 m2/g. The adsorption of MG by the biochar from Areca catechu L. peels was found to be greater than that of RB. The biochar showed an adsorption capacity of 16.113 mg/g for MG, while its capacity for RB was 15.499 mg/g. The adsorption process of biochar from Areca catechu L. peels for both MG and RB dyes follows a pseudo-second-order kinetic model.